Language learning in content-based English as a second language (ESL) classrooms - Mohamed Ismail Ahamad Shah, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2003)
The recent introduction of content-based instruction (CBI) in Malaysian schools is increasingly seen as a methodology to develop students' English language proficiency. This study presents findings from two content-based language classrooms in a Malaysian school. The study seeks to determine to what extent negative feedback and teachers' feedback focused on form were made available to the students. Feedback focused on form is considered essential for Second Language Acquisition (SLA) (Long & Robinson, 1998). Subjects for this study were two teachers and their 80 students from ESL classrooms where literature was used as content in teaching English. Audio-tape of teacher-student interaction was used to determine the extent to which such feedback was available to learners. Results of the study show that the teachers provided negative feedback and feedback focused on form consistent with theoretical claims made in SLA. However, the negative feedback and feedback focused on form provided by the teachers were minimal compared to feedback on content. Results of the study suggest that the teachers need to focus more on form, particularly. syntactic forms, when providing feedback.